Analisis Kualitas Layanan Website Pada Universitas Terbuka Palembang Menggunakan Metode Webqual 4.0 Dan Importance Performance Analysis (IPA) - Mardalena, Obi; Andryani, Ria (Journal of Information Systems and Informatics, 2021)
Website is a medium that is currently widely used as a tool to provide services and information. Palembang Open University is one of the universities that uses the website as a means to provide information related to academic activities to its students. To determine the quality of a website, it is necessary to analyze the measurement of website quality based on user perceptions. The purpose of this Analysis  is used to determine the indicators that affect the quality of website services based on the instrument used from the webqual 4.0 method which consists of 3 variables, namely usability, information quality, and service interaction quality. Then the analytical technique used is importance performance Analysis  (IPA) which will provide an overview of the indicators that need improvement or need to be maintained. The data collection technique in this study used a questionnaire with a research sample of 100 respondents. The results of the Analysis  of the quality of website services at the Open University of Palembang have a suitability level of 99.99% or
Keywords: Website Service Quality, User Satisfaction, Webqual 4.0, Importance Performance Analysis